Knock-down of LRP/LR promotes apoptosis in early and late stage colorectal carcinoma cells via caspase activation - Vania, Leila; Rebelo, Thalia M.; Ferreira, Eloise; Weiss, Stefan F. T. (BioMed Central, 2018)
Background: Cancer remains one of the leading causes of death around the world, where incidence and mortality rates are at a constant increase. Tumourigenic cells are characteristically seen to over-express the 37 kDa/67 kDa laminin receptor (LRP/LR) compared to their normal cell counterparts. This receptor has numerous roles in tumourigenesis including metastasis, angiogenic enhancement, telomerase activation, cell viability and apoptotic evasion. This study aimed to expose the role of LRP/LR on the cellular viability of early (SW-480) and late (DLD-1) stage colorectal cancer cells. Methods: siRNA were used to down-regulate the expression of LRP/LR in SW-480 and DLD-1 cells which was assessed using western blotting. Subsequently, cell survival was evaluated using the MTT cell survival assay and confocal microscopy. Thereafter, Annexin V-FITC/PI staining and caspase activity assays were used to investigate the mechanism underlying the cell death observed upon LRP/LR knockdown. The data was analysed using Student’s ttest with a confidence interval of 95%, with p-values of less than 0.05 seen as significant. Results: Here we reveal that siRNA-mediated knock-down of LRP led to notable decreases in cell viability through increased levels of apoptosis, apparent by compromised membrane integrity and significantly high caspase-3 activity. Down-regulated LRP resulted in a significant increase in caspase-8 and -9 activity in both cell lines. Conclusions: These findings show that the receptor is critically implicated in apoptosis and that LRP/LR downregulation induces apoptosis in early and late stage colorectal cancer cells through both apoptotic pathways. Thus, this study suggests that siRNA-mediated knock-down of LRP could be a possible therapeutic strategy for the treatment of early and late stage colorectal carcinoma.
Keywords: Colorectal cancer; Small interfering RNAs; Apoptosis; 37 kDa/67 kDa laminin receptor; LRP/LR; Therapeutics; SDG-3: Good health and well-being